Decoupled Glucose and Lipid Metabolic Recovery after Viral Clearance in Direct-Acting Antiviral-Treated HCV Patients: A 3-Year Prospective Cohort Study - Heng Lee (MDPI AG, 2021)
Background/Aim: The recovery pattern of hepatitis C virus (HCV)-associated metabolic alteration after sustained virological response (SVR) following direct-acting antivirals (DAAs) remains elusive. Methods: A prospective cohort study of chronic HCV-infected (CHC) patients (n = 415) receiving DAAs (n = 365) was conducted. Metabolic profiles were examined in SVR patients (n = 360) every 3–6 months after therapy and compared with those of sex- and age-matched controls (n = 470). Results: At baseline, of 415, 168 (40.5%) had insulin resistance (IR). The following were associated: levels of high-density lipoprotein cholesterol (HDL-C), triglycerides (TGs), HCV RNA, fibrosis-4 score, and interferon-λ3-rs12979860 genotype with total cholesterol (TC) levels; and TG levels and BMI with HOMA-IR. Over a 3-year follow-up, in SVR patients, BMI and TC levels and TG/HDL-C ratios increased from baseline, while HOMA-IR trended downward by 72 weeks after therapy and then increased. The increased HDL-C levels began to decrease after 72 weeks after therapy. TC and HOMA-IR were negatively associated with each other until 24 weeks after therapy. Earlier increases in BMI and decreases in HOMA-IR were noted in SVR patients with than in those without baseline IR. Compared with controls, in the subgroup without baseline IR, SVR patients had increased BMI and HOMA-IR levels. Metabolic profiles were similar between SVR patients and controls in the subgroup with baseline IR. Conclusions: In SVR patients treated with DAAs, the recovery of altered lipid and glucose metabolism was not coupled until 72-week post-therapy, when HOMA-IR reached its nadir. SVR patients with baseline IR recovered from HCV-associated metabolic alterations earlier than those without baseline IR.